APPLICATION OF DEBATE METHOD TO IMPROVE SPEAKING ABILITY OF STUDENTS OF SMAN 1 GALIS PAMEKASAN - Yuliarsih, Yuliarsih; Zuhri, Muhammad Darrin; Wahyuli, Sabrina (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the effectiveness of the debate method in improving the speaking skills of grade XI students at SMAN 1 Galis Pamekasan. Speaking skills are one of the important competencies in education, but they are often overlooked in conventional learning. This study uses a Classroom Action Research (PTK) design which is carried out in two cycles. Each cycle involves the stages of planning, implementation, observation, and reflection. The subjects of the study were 30 grade XI students, with data obtained through observation sheets, speaking skills assessment rubrics, and documentation. Data analysis was carried out using qualitative and quantitative descriptive methods. The results showed that the debate method significantly improved students' speaking skills. The average speaking skill score increased from 65 in the initial condition to 82 after two cycles. This improvement can be seen in the aspects of fluency, clarity, and proper use of vocabulary. Observations also showed that students became more confident and active in participating. The debate method is not only effective in improving speaking skills, but it also encourages students to think critically and work collaboratively. This study concludes that the debate method is an effective learning strategy and can be widely implemented in secondary schools. Teachers are advised to make debate a part of their learning routine, with relevant topics and clear guidance. Further research is recommended to explore the application of debate methods at different levels of education and their impact on long-term communication skills.